DNA Sequence Reconstruction Based On Genetic Algorithm - Islam, Md. Rafiqul; Shahriar, Md. Rowshan; Mohammad Shaheed, Abul Faisal (Malaysian Journal of Computer Science, 2008)
It is becoming increasingly important to develop a novel process for determining the letters of our genetic code, known as DNA sequencing. This task is performed by large datasets using the combination of heuristic methods with little mathematical calculation. In this paper, we present a new method for DNA sequence reconstruction using genetic algorithm, which is able to predict the actual DNA sequence. The performance of the genetic algorithm is evaluated with respect to previous methods in the literature. The results indicate that the proposed new method is superior to previous methods. Finally we compare the results of the experiment and discuss the performance of the proposed method in the DNA sequence reconstruction.